2020
DOI: 10.21203/rs.3.rs-22227/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of ambient air pollutants and meteorological factors on COVID-19 transmission

Abstract: Background Since its first appearance in Wuhan China in December 2019, the coronavirus disease 2019 (COVID-19) has become a worldwide pandemic. Although the COVID-19 is known to cause by human-to-human transmission, it remains largely unclear whether ambient air pollutants and meteorological factors could promote its transmission process. Methods We conducted a retrospective cohort study to understand the correlation between COVID-19 incidence and eight ambient air pollutants (PM2.5, PM10, SO2, CO, NO2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Indeed, the body of scientific evidence is growing. Several studies so far investigated the impact of spatial differences in air pollution [17][18][19][20][21][22][23][24][25][26][27][28][29] and others have looked into short-term temporal air pollution effects [30][31][32][33][34][35][36][37]. Several possible mechanisms have been proposed that would explain associations between acute and chronic air pollution and COVID-19 risk of infection and of mortality [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the body of scientific evidence is growing. Several studies so far investigated the impact of spatial differences in air pollution [17][18][19][20][21][22][23][24][25][26][27][28][29] and others have looked into short-term temporal air pollution effects [30][31][32][33][34][35][36][37]. Several possible mechanisms have been proposed that would explain associations between acute and chronic air pollution and COVID-19 risk of infection and of mortality [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…As well as for particulates matter, but the paper of Ma et al, (2020) provides different findings, reporting no association between NO2 and mortality rate in in Wuhan, China. Guan et al (2020) and Zhu et al (2020), by applying the same method explained for PM, observed that the COVID-19 incidence follows a positive pattern association with NO2 in the city of Wuhan (R 2 = 0.329 and p<0.001) and XiaoGa (R 2 =0.158 and p<0.05), and that a 10-μg/m 3 increase (lag0-14)…”
Section: Nitrogen Dioxide (No2)mentioning
confidence: 95%
“…First observations report a positive association between ambient concentrations of NO2 and COVID-19 pandemic across Europe, China and U.S.A (Guan et al, 2020;Ogen, 2020;Pansini and Fornacca, 2020;Travaglio et al, 2020;Yao et al, 2020a;Zhu et al, 2020). As well as for particulates matter, but the paper of Ma et al, (2020) provides different findings, reporting no association between NO2 and mortality rate in in Wuhan, China.…”
Section: Nitrogen Dioxide (No2)mentioning
confidence: 99%
See 2 more Smart Citations